Letter - Azcárate, Pablo de, 1890-1971
030-0077-001 EMBAJADA DE ESPAÑA London, September 2nd., 1938. Dear Sir, I have pleasure in informing you that in order to make the best possible use of the generous donations received from all organizations abroad for the alleviation of the sufferings of the Spanish civilian population, to ensure their adequate distribution in accordance with the personal desires of the donors, and to supply the latter with all the information they may require, a Committee known as the "Comité Nacional de Ayuda a España" (National Committee for Assistance to Spain), has been formed. This Committee is entrusted with the task of co-ordinating all the entities engaged in Spanish relief work, and in order to keep in touch with the various British organisations of this nature, a Secretary of this Embassy has been appointed as special delegate in London. This delegate will be in direct communication with the relevant Spanish authorities, and will act as intermediary between them and the organisations in Great Britain who are carrying on their humanitarian work on behalf of the Spanish people. The official appointed is Mr. Daniel Fernández-Shaw, Commercial Attaché to this Embassy, whose office is at 2, Cavendish Square, London, W.1. (2nd. Floor); Tel. No. Lan. 3671. You will shortly receive a visit from Mr. Fernández-Shaw, who is most anxious to help your organisation and you personally in all questions related to Spanish relief work. I sincerely hope that you and Mr. Fernández-Shaw may be of mutual assistance to one another in all such matters. I should be most grateful if you would kindly inform any Trades Union organisations interested in Spanish relief work, of the contents of this letter. Yours truly, P. Azcarate Spanish Ambassador. V . Tewson, Esq. , Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/30/77